Issues of Group Settlement’s Land Inheritance Management in Peninsular Malaysia - Mohd Asri, Mohammad Hazim Firdaus; Maamor, Selamah; Mohd Noor, Fauziah (Lembaga Zakat Negeri Kedah, 2022)
The transfer of wealth after one’s death is an essential matter in Islam as the religion emphasizes the paramountcy of lawful ownership. Therefore, the inherited wealth should be distributed to the rightful heir to benefit and live a comfortable life. The study aims to review the inheritance management issues in the group settlement through a literature study. The previous works of literature are analysed using content analysis for the issues they conveyed other than the purpose, methodology of the study, and the finding. The study found that there is quite some literature throughout times discussing the inheritance administration problem as well as the planning instrument in distributing the deceased estate in the research area. However, the specific study that points to the issues of group settlement in Malaysia has limited publications, although the notable problems are not solved thoroughly. Despite that, three main issues of group settlement’s land inheritance management are identified: lack of population knowledge on the inheritance practice, inefficient system and relay of information, and Group Settlement Act (GSA) 1960 restrictions. As a result, there is a delay in commencing the inheritance management by the beneficiaries